The Application of Environmentally Friendly Technology for Student Learning Materials at SMA Tunas Mekar Indonesia Bandar Lampung - Oktavia, Amalia; Marvie, Ilham; Iqbal, Muhammad (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2023)
High school students are one of the objects in introducing and understanding environmentally friendly technologies such as the development of solar panel tools and rainwater harvesting tools. Bandar Lampung is one of the cities that receive up to 9 hours of long sun in the summer and has high rainfall during the rainy season. Therefore, this community service program can be a means to bring this technology into the school learning process. This program aims to increase the interest of SMA Tunas Mekar Indonesia students in learning environmentally friendly technology; besides that, this activity also aims to increase students' understanding of the importance of applying solar panel technology and rainwater harvesting equipment. The method used consists of the observation stage, analysis stage, the tool's planning and design, and implementation and evaluation stages. Based on the pre-test and post-test results given during the training, this program succeeded in increasing interest and increasing students' understanding of the importance of implementing environmentally friendly technologies.